Wound Healing Potency of Edible Bird’s Nest - Alysia, Jessica; Stella, Maureen Miracle; Widjaja, Maureen; Wijaya, Lorettha (GLOBAL HEALTH SCIENCE GROUP, 2025)
Edible bird's nest (EBN) or swiftlet's nest has recently been used extensively in regenerative medicine. This study aims to give a more thorough overview on the efficacy of EBN as a wound-healing agent. Method: We searched literature through several databases: Google Scholar, PubMed, Proquest, JSTOR, EBSCOhost, and SAGE. The keywords used were